A Review of haptic feedback in virtual reality for manufacturing industry - Abdul Aziz, Faieza; Mousavi, Maryam (Transaction of the Mechanical Engineering Division of the Institition of Engineers, Bangladesh, 2009)
This paper discusses the application of haptic feedback in Virtual Reality to enhance user performance in manufacturing industry. Haptic interfaces have the potential to enhance communication and interaction via the computer enabling affective expressive interpersonal communication and enriching interaction by haptic feedback. The aim of this study was to investigate and develop a better understanding of using haptic feedback in manufacturing.